Preparation of modified ceramic membranes with silica sol-dip coating for separation biogas application - Mohd Daud, Farah Diana; Zulianey Kahlib, Nor Amyra; Mel , Maizirwan; Ahmad Azhar, Ahmad Zahirani; Hassan , Noor Azlina (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Atmospheric CO2 emissions are considered as the greatest environmental challenge the world is facing today. This concern has been improved due to recent advances in materials process engineering resulting in the development of inorganic gas separation membrane with excellent thermal and mechanical stability required for most gas separations. Membrane separation of gases is a highly complex process and therefore the material used for its preparation should exhibit a long-lasting characteristic, stability and modify in an advanced manner to be adapted to separate specific gases. Thus, in this paper, the modified ceramic membranes with silica sol dip-coating have been prepared by using tetraethylorthosilicate (TEOS), distilled water and ethyl alcohol as sol. The influences of dipping time have been examined. The surface and cross section morphologies of the membranes were analyzed using Scanning Electron Microscopy (SEM). It was found that the pore size of the modified ceramic membrane obtained decreased with increasing dipping time.